HUBUNGAN ANTARA MINAT BELAJAR SISWA DENGAN HASIL BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DAN VIII SMP WAHID HASYIM TAHUN AJARAN 2021/2022 - Fauziah Qhotrun Nada (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Many things affect level student learning outcomes, ranging from internal factors and external factors. Student internal can trigger the high and low student learning outcomes. Great interest in learning tends to produce high learning outcomes, otherwise less produce low. is level of student, the level of student learning outcomes, and interests and student learning outcomes in Islamic Education Class VII and VIII at Wahid H The population was taken from all students in grades VII and VII which totaled 148 students. The data collection uses a questionnaire and the value of the Final Semester Exam. Hypothesis testing using Spearman Rank Correlation. Data analysis l 2010 program and SPSS Version 2. showed interest in learning interest factors affecting the literacy program, a teaBcher's performance factor, internal factors, namely feelings of pleasure, student experience factors, encouragement factors. from parents, and peer factors. For the level of student learning outcomes in the very good category, with factors that influence interest in learning, peer factors, learning style factors, teacher performance factors, and facilities that are quite good from the school. The results of hypothesis testing stated was a positive in learning and the learning outcomes of class VII and VIII students of SMP Wahid Hasyim Malang City. It is evident from the results of the Spearman Rank analysis 0.029 <0.05. rank correlation yield a value of -0.587, which refers to the Spearman Rank Correlation Coefficient Guidelines table in the interval 0.40 – 0.599 which means that the level of relationship between the two variables is quite strong.